Interventions Targeting Smoking Cessation for Patients With Chronic Pain: An Evidence Synthesis. Issue 1 (23rd November 2018) - Saragiotto, Bruno T; Kamper, Steven J; Hodder, Rebecca; Silva, Priscilla V; Wolfenden, Luke; Lee, Hopin; Oliveira, Vinicius C; Robson, Emma; Wiggers, John; Williams, Christopher M
Abstract: Introduction: Smoking is a risk factor for chronic pain conditions. Epidemiological evidence suggests that smoking cessation may be an important treatment target in people with chronic pain. The aim of this study was to examine the effectiveness of smoking cessation interventions in people with chronic pain. Methods: We systematically searched for clinical trials investigating the effectiveness of smoking cessation interventions for people with chronic pain, compared with any control comparator. Primary outcomes were pain and physical function. Secondary outcomes were smoking status, quality of life, psychological and cognitive function, and adverse events. We assessed risk of bias using the Cochrane Risk of Bias criteria and the quality of evidence with GRADE. Results: Searches retrieved 3845 records and identified two trials for inclusion (total n = 99 participants). There was low-quality evidence of no effect of smoking cessation programs on pain and very low-quality evidence of no effect on function at short-term follow-up. There was conflicting evidence on the effect of smoking cessation interventions for changing the smoking status and number of cigarettes consumed per day. There was no effect on depression and anxiety. Conclusion: Current evidence does not indicate clinically important effects of smoking cessation interventions in people with chronic pain. There is a need for high-quality trials in this area. Implications: Our review highlights an important evidence gap. We found only two studies investigating smoking cessation programs for chronic pain conditions providing very low- to low-quality evidence.